Sensores eletroquímicos contendo supramoléculas de complexos periféricos de rutênio: obtenção e aplicações - Silva, Monize Martins da (Universidade Federal de São Carlos, 2013)
In this work were performed the reaction of the 5, 10, 15, 20- (tetrapyridil)porphyrin (TPyP) with the cations: Mn(III), Zn(II), Fe(III) and Ga(III) promoting the insertion of these metals in the porphyrin ring center. The reaction of these porphyrins (both, in free base form and in metallated form) were carried out with the complex mer-[RuCl3(dppb)(H2O)], resulting in the supramolecular species, {TPyP[RuCl3(dppb)]4} and {M-TPyP(H2O)2[RuCl3(dppb)]4}+ (M= Mn, Zn, Fe and Ga). The products were characterized by absorption spectroscopy in the UV-Vis and IR regions, elemental analysis (C, H, N), EPR, cyclic and differential pulse voltammetry, conductivity and magnetic susceptibility. In order to investigate the formation of films on the surface of a glassy carbon electrode the electropolymerization of the polymetallated porphyrins was performed, aiming to produce an electronically modified electrode. The carbon paste was also modified, using the same supramolecules. The modified glassy carbon electrodes were used as electrochemical sensors for determination and quantification of acetaminophen and dopamine substrates, which showed better results, when compared with unmodified glassy carbon electrode. The results obtained presents low DL and QL values. All modified electrodes were effective in quantifying the substrates, using real samples, with a relative standard deviation of less than 1.0%, showing good sensibility and reproducibility. The modified carbon paste electrodes (MCPEs) were used as electrochemical sensors for determination and quantification of real samples of paracetamol and sildenafil citrate (Viagra ®), showing good sensibility and reproducibility. The results obtained with MCPEs showed better results than with unmodified electrode. The relative standard derivation was less than 2.5%. In order to compare with the electrochemical method, a CLAE method was developed. The accuracy of the results obtained using both modified glassy carbon and carbon paste electrodes, were confirmed.
Keywords: Química inorgânica; Sensores eletroquímicos; Porfirina; Supramoléculas; Rutênio; CIENCIAS EXATAS E DA TERRA::QUIMICA